Titles of Memoir and Autobiographical Texts about First World War: “War Captivity” Frame - P. P. Banman (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The article is devoted to the analysis of the “Kriegsgefangenschaft” / “War Captivity” frame, the identification of its slots and their filling based on the headings of German-language memoir and autobiographical texts written by prisoners of war of the First World War. It is noted that these materials did not become the subject of a wide study of Russian-speaking researchers. The author draws attention to the fact that headings, being a strong position of the text, are aimed at attracting the attention of a potential recipient. It has been established that in the course of the author’s semantization, the concept of “captivity” is subject to rethinking: places of stay in captivity (Russia, Siberia) are described as disastrous: the camps become a prison for prisoners of war who, despite the existence of conventions protecting their rights, turn into convicts. It is shown that the slot “time” implies either an exact indication of the historical period (the years of the First World War), or the duration of being in captivity; in isolated cases, we are talking about the age and period of a person’s life. It has been established that the “agent” slot is filled with anthroponyms, indicating nationality, position, rank, profession. The author comes to the conclusion that the identified slots get their further implementation at the text level.